The influence of leadership style, business ethics, and environmental performance toward corporate social performance and its impact on corporate financial performance - Hasbu, Wiyas Yulias; Zarkasyi, Wahyudin; Suharman, Harry; Poulus, Sugiono (International Journal of Management and Sustainability, 2024)
The study presents research clarifying the influence of leadership style, business ethics, and environmental performance on corporate social performance and its implications for corporate financial performance. A survey was done in manufacturing companies of Indonesia’s State Own Enterprise (SOE) and affiliates. Corporate performance is not solely directed towards shareholders or exclusively defined by financial measures; rather, it encompasses a focus on the impact of the organization on the society in which it operates. The style of leadership plays a crucial role in influencing the strategic management process, enabling the organization to implement successful strategies to realize its vision. Business ethics provide advantages to companies by fostering a favorable influence on their competitive edge in the corporate landscape. Environmental concerns are gaining growing significance among various corporate stakeholders, encompassing consumers, shareholders, prospective investors, creditors, regulatory bodies, employees, and the wider public. The finding of the study was that a leadership style had a positive influence on corporate social performance but a negative influence on corporate financial performance. Business ethics had a negative influence on financial performance but a positive influence on corporate social performance and environmental performance. Environmental performance had a negative influence on corporate social performance but positive influence on financial performance. Corporate social performance has a positive influence on corporate financial performance.